O direito fundamental à razoável duração do processo penal e a prescrição da pretensão punitiva - Braga, Hans Robert Dalbello (2015)
The research Examines the fundamental right to reasonable duration of the criminal process under the Article 5, paragraph LXXVIII of the Federal Constitution, by the text of the Constitutional Amendment nº 45/2004, with the aim of (re) think their legal interpretation, of the punitive preintention prescription. The study covers the analysis of reasonable duration of the criminal process and its underlying approach to the institution of criminal prescription. To investigate the possibility of the fit of both theories between the two concepts. At first are considered the conceptions of time (absolute and relative) and their intimate relationships with the law, more specifically with the criminal procedural law, considering that all procedural acts are governed by lapse of time. In a second moment is directly addressed the fundamental right to duration of the criminal process and its current hermeneutics inaccuracy. Thus, it held a brief analysis of the doctrine of the fixed term and also the doctrine of non-term as well as the legal consequences and solutions proposed by the academy in the case of non-observance of reasonable time. The third moment it is analised the criminal prescription and the theories that give it grounds for the legitimacy, as well as the nefarious institution of criminal imprescriptibility. At the end it is examined the possibility of the punitive preintention to limitade the period of reasonable duration of the criminal process, taking into perspective the concepts of time previously developed. The research employed the deductive method and the research through the literature.